(untitled) (International journal of artificial intelligence, 2025)
The article analyzes the role of nutritional factors in the pathogenesis and course of skin diseases from a hygienic point of view. Analysis of the literature of recent years shows that a "Western" diet with a high glycemic load, ultra-processed products, excessive consumption of animal fats and sugar contribute to the development and exacerbation of inflammatory skin diseases, such as acne, psoriasis, and atopic dermatitis. Conversely, a Mediterranean-style diet rich in fruits, vegetables, whole grains, fish fatty acids, and polyphenols can improve skin condition through its antioxidant and anti-inflammatory effects. From the point of view of a hygienic assessment, the need for a systematic study of the diet of patients with skin diseases, the identification of nutritional errors, and the development of evidence-based recommendations for diet therapy is substantiated.